Characterization and chemoresistance of HT29 (Colon cancer) and TW06 (Nasopharyngeal cancer) tumorspheres - Goh, Iris Wen Li (2014)
The cancer stem cell (CSC) hypothesis states that these subpopulation of cells are responsible for the initiation of tumor and its recurrence. It has been shown that these cancer stem cells can be enriched in-vitro as tumorspheres under serum-free conditions. The objectives of this study is to establish and characterize the tumorspheres generated from a colon adenocarcinoma cell line (HT29) and a nasopharyngeal carcinoma cell line (TW06), and also to evaluate the chemoresistance properties of these tumorspheres of these cells. Here, two cell lines were grown as tumorspheres in vitro in serum-free DMEM/F12-supplemented medium with methylcellulose and plated on poly(2-hydroxyethyl methacrylate)-coated plates. Flow cytometric studies were performed to evaluate the surface markers expression of the tumospheres. Reverse-transcription-qPCR was also conducted to evaluate the expression level of cancer stem cell-related genes. Also, chemotoxicity assay was carried out to evaluate the chemoresistant properties of these tumorspheres to chemotherapeutic agents. In this study, it was found that both TW06-passage 0 and late passage tumorspheres had higher percentage of CD44+/CD24-/EpCAM+ population compared to parental adherent cells. HT29 only show differences in terms of CD133 expression where only HT29-late passage tumorspheres were found to have higher CD133+ population. In addition, the expression of both SOX2 and ALDH1A3 was significantly lower in the passage 0 and late passage TW06 tumorspheres while the expression of Bmi1 is much higher in the late passage TW06 tumorsphere. A lower expression of the Bmi1 gene was found in the late passage tumorsphere of HT29. Chemotoxicity assay result showed that the TW06-late passage tumorspheres was resistant towards docetaxel at concentrations at or below 2.5 times of IC50 but not at higher concentrations. As for the HT29 tumorspheres, it was found that a few tumorspheres from passage 0 was able to survive oxaliplatin treatment and its size appeared to be much larger as compared to the untreated tumorspheres. The DTX resistant tumorspheres of TW06 (TW06-DTX-R) and OXA resistant tumorspheres of HT29 (HT29-OXAR) were isolated and then cultured with DTX and OXA respectively for further evaluation of their chemoresistant properties. Both cell cycle assay and apoptosis assay further confirmed that TW06-DTX-R generated from TW06-late passage tumorspheres showed resistance towards docetaxel and HT29-OXA-R generated from HT29-parental tumorspheres were resistant to the oxaliplatin treatment. Finally, this study concluded that serially passaged tumorspheres may be enriched in cancer stem cells and were towards specific chemotherapeutic agents.